opepayflarpws

2022-06-22

I've been working on this question but just can't crack it. It is as follows.

Using $\frac{dy}{dx}=\frac{a\sqrt{{x}^{2}+{y}^{2}}+by}{bx}$ where y(1)=0

and by letting $v=\frac{y}{x}$ transform the above differential equation to an equation in v and x. Find the implicit solution of the resulting separable equation. Then use the relationship y=xv to obtain $y+\sqrt{{x}^{2}+{y}^{2}}={x}^{\frac{a}{b}+1}$

I've tried separate the upper terms into two fractions which makes the second term simply $\frac{by}{bx}=v$ but I am still left with the nasty square root with the y on the inside and I can't shift it easily to solve as a first order DE. Also I was thinking about solving it as a linear first order ODE but we have a squared term. Sorry about formatting as well, first time posting a question.

Using $\frac{dy}{dx}=\frac{a\sqrt{{x}^{2}+{y}^{2}}+by}{bx}$ where y(1)=0

and by letting $v=\frac{y}{x}$ transform the above differential equation to an equation in v and x. Find the implicit solution of the resulting separable equation. Then use the relationship y=xv to obtain $y+\sqrt{{x}^{2}+{y}^{2}}={x}^{\frac{a}{b}+1}$

I've tried separate the upper terms into two fractions which makes the second term simply $\frac{by}{bx}=v$ but I am still left with the nasty square root with the y on the inside and I can't shift it easily to solve as a first order DE. Also I was thinking about solving it as a linear first order ODE but we have a squared term. Sorry about formatting as well, first time posting a question.

assumintdz

Beginner2022-06-23Added 22 answers

Just as you did

$\frac{dy}{dx}=\frac{a\sqrt{{x}^{2}+{y}^{2}}+by}{bx}$

Let

$y=xv\phantom{\rule{thickmathspace}{0ex}}\u27f9\phantom{\rule{thickmathspace}{0ex}}{y}^{\prime}=v+x{v}^{\prime}$

making the equation to be

$x{v}^{\prime}=\frac{a}{b}\sqrt{1+{v}^{2}}$

which is separable

$\int \frac{dx}{x}=\frac{b}{a}\int \frac{dv}{\sqrt{1+{v}^{2}}}$

making

$\mathrm{log}(x)+C=\frac{b}{a}{\mathrm{sinh}}^{-1}(v)$

So

$v=\mathrm{sinh}(\frac{a}{b}\mathrm{log}(x)+C)\phantom{\rule{thickmathspace}{0ex}}\u27f9\phantom{\rule{thickmathspace}{0ex}}y=x\phantom{\rule{thinmathspace}{0ex}}\mathrm{sinh}(\frac{a}{b}\mathrm{log}(x)+C)$

$\frac{dy}{dx}=\frac{a\sqrt{{x}^{2}+{y}^{2}}+by}{bx}$

Let

$y=xv\phantom{\rule{thickmathspace}{0ex}}\u27f9\phantom{\rule{thickmathspace}{0ex}}{y}^{\prime}=v+x{v}^{\prime}$

making the equation to be

$x{v}^{\prime}=\frac{a}{b}\sqrt{1+{v}^{2}}$

which is separable

$\int \frac{dx}{x}=\frac{b}{a}\int \frac{dv}{\sqrt{1+{v}^{2}}}$

making

$\mathrm{log}(x)+C=\frac{b}{a}{\mathrm{sinh}}^{-1}(v)$

So

$v=\mathrm{sinh}(\frac{a}{b}\mathrm{log}(x)+C)\phantom{\rule{thickmathspace}{0ex}}\u27f9\phantom{\rule{thickmathspace}{0ex}}y=x\phantom{\rule{thinmathspace}{0ex}}\mathrm{sinh}(\frac{a}{b}\mathrm{log}(x)+C)$

- A body falls from rest against resistance proportional to the square root of the speed at any instant. If the body attains speed V1 and V2 feet per second, after 1 and 2 seconds in motion, respectively, find an expression for the limiting velocity.

The Laplace transform of the product of two functions is the product of the Laplace transforms of each given function. True or False

The Laplace transform of

is$u(t-2)$

(a)$\frac{1}{s}+2$

(b)$\frac{1}{s}-2$

(c) ??$e}^{2}\frac{s}{s}\left(d\right)\frac{{e}^{-2s}}{s$ 1 degree on celsius scale is equal to

A) $\frac{9}{5}$ degree on fahrenheit scale

B) $\frac{5}{9}$ degree on fahrenheit scale

C) 1 degree on fahrenheit scale

D) 5 degree on fahrenheit scaleThe Laplace transform of $t{e}^{t}$ is A. $\frac{s}{(s+1{)}^{2}}$ B. $\frac{1}{(s-1{)}^{2}}$ C. $\frac{s}{(s+1{)}^{2}}$ D. $\frac{s}{(s-1)}$

What is the Laplace transform of

into the s domain?$t\mathrm{cos}t$ Find the general solution of the given differential equation:

${y}^{\u2033}-2{y}^{\prime}+y=0$The rate at which a body cools is proportional to the difference in

temperature between the body and its surroundings. If a body in air

at 0℃ will cool from 200℃ 𝑡𝑜 100℃ in 40 minutes, how many more

minutes will it take the body to cool from 100℃ 𝑡𝑜 50℃ ?A body falls from rest against a resistance proportional to the velocity at any instant. If the limiting velocity is 60fps and the body attains half that velocity in 1 second, find the initial velocity.

What's the correct way to go about computing the Inverse Laplace transform of this?

$\frac{-2s+1}{({s}^{2}+2s+5)}$

I Completed the square on the bottom but what do you do now?

$\frac{-2s+1}{(s+1{)}^{2}+4}$How to find inverse Laplace transform of the following function?

$X(s)=\frac{s}{{s}^{4}+1}$

I tried to use the definition: $f(t)={\mathcal{L}}^{-1}\{F(s)\}=\frac{1}{2\pi i}\underset{T\to \mathrm{\infty}}{lim}{\int}_{\gamma -iT}^{\gamma +iT}{e}^{st}F(s)\phantom{\rule{thinmathspace}{0ex}}ds$or the partial fraction expansion but I have not achieved results.How do i find the lapalace transorm of this intergral using the convolution theorem? ${\int}_{0}^{t}{e}^{-x}\mathrm{cos}x\phantom{\rule{thinmathspace}{0ex}}dx$

How can I solve this differential equation? : $xydx-({x}^{2}+1)dy=0$

Find the inverse Laplace transform of $\frac{{s}^{2}-4s-4}{{s}^{4}+8{s}^{2}+16}$

inverse laplace transform - with symbolic variables:

$F(s)=\frac{2{s}^{2}+(a-6b)s+{a}^{2}-4ab}{({s}^{2}-{a}^{2})(s-2b)}$

My steps:

$F(s)=\frac{2{s}^{2}+(a-6b)s+{a}^{2}-4ab}{(s+a)(s-a)(s-2b)}$

$=\frac{A}{s+a}+\frac{B}{s-a}+\frac{C}{s-2b}+K$

$K=0$

$A=F(s)\ast (s+a)$